2009
DOI: 10.1111/j.1475-679x.2009.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Investors' Opinion Divergence

Abstract: Numerous proxies for divergence of investors' opinions have been suggested in the empirical accounting and finance literatures. I offer a new proxy constructed from proprietary limit order and market order data. This allows me to capture additional information on investors' private valuations. Proxies from the extant literature, based on publicly available data, do not contain such information. Given my new measure, I ask which of the extant proxies correlates best with it. In my regression analysis, unexplain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
115
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(115 citation statements)
references
References 85 publications
(157 reference statements)
0
115
0
Order By: Relevance
“…The robustness of Beaver"s (1968) finding was further established by a series of studies (e.g., Bamber 1987, Bamber and Cheon 1995, Garfinkel and Sokobin 2006, Garfinkel 2009, D"Agusta et. al.…”
Section: Investor Disagreement and Trading Volumementioning
confidence: 99%
“…The robustness of Beaver"s (1968) finding was further established by a series of studies (e.g., Bamber 1987, Bamber and Cheon 1995, Garfinkel and Sokobin 2006, Garfinkel 2009, D"Agusta et. al.…”
Section: Investor Disagreement and Trading Volumementioning
confidence: 99%
“…Because the literature has shown that unexpected volume strongly reflects divergence in investors' opinions (Garfinkel, 2009), I extract institutional investors' heterogeneous beliefs from the unexpected trading volume. Garfinkel (2009) compares unexpected trading volume to other proxies from the extant literature and claims that the unexpected trading volume is the best proxy for heterogeneous beliefs.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…In addition, the excess returns derived from an arbitrage portfolio constructed based on the level of heterogeneous beliefs cannot be explained by risk factors such as the market's risk, size and value (Chen et al, 2015). In prior empirical research, differences of opinion among investors are generally viewed as a proxy for heterogeneous beliefs, the 7784 heterogeneity proxies fall into two separate categories: (1)Analysts' forecast characteristics-dispersion in analysts' earnings forecasts (Diether et al, 2002); (2)The other proxies focusses directly on investors' trades, like as unexpected trading volume (Garfinkel and Sokobin, 2006), stock return volatility (Ang et al, 2006), turnover (Boehme et al, 2006), investor orders (Garfinkel, 2009) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Following Garfinkel and Sokobin (2006), Hong and Stein (2007), and Garfinkel (2009), we use estimates from trading volume to estimate the divergence of opinion amongst a firm's investors. Our results suggest that the investors of repurchasing firms have higher divergence of opinion on their holding firm's value than the investors of non-repurchasing firms.…”
Section: ~ 24 ~mentioning
confidence: 99%